2008
DOI: 10.1186/1471-2474-9-59
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of accelerated perioperative care and rehabilitation intervention compared to current intervention after hip and knee arthroplasty. A before-after trial of 247 patients with a 3-month follow-up

Abstract: Background: In Denmark, approximately 12,000 hip and knee arthroplasties were performed in 2006, and the hospital costs were close to US$ 110,000,000. In a randomized clinical trial, we have recently demonstrated the efficacy of accelerated perioperative care and rehabilitation intervention after hip and knee arthroplasty compared to current intervention under ideal circumstances. We do not, however, know whether these results could be reached under usual circumstances of healthcare practice. We therefore inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 20 publications
3
71
1
3
Order By: Relevance
“…Realising that the surgical journey involves many professional competencies, a more integrated, multiprofessional, multidisciplinary approach was needed, whereby a decision taken early in the course of the treatment plan would impact on later developments and influence the choices available for recovery further down the line. Unfortunately, large gaps still exist between what the evidence suggests should happen and what actually happens in practice 1, 3…”
Section: Figurementioning
confidence: 99%
“…Realising that the surgical journey involves many professional competencies, a more integrated, multiprofessional, multidisciplinary approach was needed, whereby a decision taken early in the course of the treatment plan would impact on later developments and influence the choices available for recovery further down the line. Unfortunately, large gaps still exist between what the evidence suggests should happen and what actually happens in practice 1, 3…”
Section: Figurementioning
confidence: 99%
“…Accelerated rehabilitation protocols are another strategy to reduce cost and improve outcomes during the inpatient period. These protocols can reduce LOS, improve outcomes, and are estimated to save approximately $4000 per patient [61,62]. A 2008 Cochrane review supports implementation of multidisciplinary clinical pathways, including early postoperative rehabilitation [63].…”
Section: Optimizing Quality and Reducing Costmentioning
confidence: 99%
“…Increased PROMS were reported by Larsen et al [11,20,21] that early mobilization, a nurse-led organization and optimization of the preoperative education were a possible reasons for these improved PROMs [11,20,21]. Our preoperative education and postoperative organization was unchanged.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, a possible explanation for our results could be the strict patient selection criteria to select patients into one of the two clinical pathways. Besides, the results of Larson et al were found after TKA in an enhanced recovery pathway [11,20,21], data after outpatient surgery are lacking. Hoorntje et al [12] recently published their case-controlled study regarding the presence of symptoms of anxiety and depression, by means of the Hospital Anxiety and Depression Scale (HADS) in patients operated after UKA.…”
Section: Discussionmentioning
confidence: 92%